2014
DOI: 10.3399/bjgp14x680989
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences of using a smartphone application to increase physical activity: the SMART MOVE qualitative study in primary care

Abstract: BackgroundRegular physical activity is known to help prevent and treat numerous non-communicable diseases. Smartphone applications (apps) have been shown to increase physical activity in primary care but little is known regarding the views of patients using such technology or how such technology may change behaviour.AimTo explore patients’ views and experiences of using smartphones to promote physical activity in primary care.Design and settingThis qualitative study was embedded within the SMART MOVE randomise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 21 publications
5
63
0
2
Order By: Relevance
“…Recently, mobile phone applications have delivered health promotion interventions and services successfully such as regulation of physical activity [13][14][15][16] , mental health monitoring 15 , nutrition and diet improvement 17,18 . One comparative study suggested a large number of smokers use the smartphone to send and receive texts, download apps, use Facebook, and browse health-related internet sites 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mobile phone applications have delivered health promotion interventions and services successfully such as regulation of physical activity [13][14][15][16] , mental health monitoring 15 , nutrition and diet improvement 17,18 . One comparative study suggested a large number of smokers use the smartphone to send and receive texts, download apps, use Facebook, and browse health-related internet sites 19 .…”
Section: Introductionmentioning
confidence: 99%
“…A small number of experimental studies have found QOS approaches, when compared to similar non-QOS alternatives, have a stronger impact on motivating users toward their health and wellness goals (Cadmus-Bertram et al 2015;Casey et al 2014;Pettinico and Milne 2017). Work by Pettinico and Milne (2017) provides a theoretical framework for the positive impact of QOS on goal-directed motivation, based on goal-setting theory (Latham and Yukl 1975;Locke and Latham 1990).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Beyond the "top-down" norms mentioned above, users themselves have specified numerous criteria for a positive experience of using mobile PA and FT apps. The most prominent expectations of users are (Casey et al, 2014;Kari et al, 2016;Tang et al, 2016;Wang et al, 2016;Kettunen, Critchley & Kari, 2019):…”
Section: Connection To Social Network and Communitiesmentioning
confidence: 99%